Crossing the Boundaries of Film Aesthetics: Challenging Avant-Garde Practices and Contemporary Cinema Exhibitions in Indonesia - Pauhrizi, Erik Muhammad; Ernawan, Erika; Warsana, Dedi; Soetedja, Zakarias S.; Utama, Rizki Resa; Alfathadiningrat, Danendra (Universitas Negeri Semarang, 2025)
This study investigates the impact of avant-garde cinema in redefining Indonesian film aesthetics, focusing on its role in challenging dominant cultural and technological narratives in the digital era. Presented at the Cine Future: Radical Cinema on Future Perspective exhibition, the research identifies a critical gap in mainstream cinema’s limited engagement with narratives evolving alongside rapid advancements in projection technology and digital reproduction. The study is anchored in the experimental works of film students from Universitas Pendidikan Indonesia’s Film and Television Study Program, showcased in the Cine Future exhibition, which exemplifies avant-garde cinema’s potential to reinterpret traditional narratives. With the Practice-led Research methodology, this research integrates artistic practice with critical analysis, allowing student filmmakers to explore the complexities of the digital age through creative expression. Findings indicate that avant-garde cinema enables the construction of new, culturally rooted narratives by merging historical aesthetics with modern technology, providing students with a framework for critiquing and interpreting social realities. This research contributes to broader discussions on avant-garde cinema’s relevance in academic and creative fields. It demonstrates its significance in fostering critical dialogue and evolving cinema as a dynamic medium for cultural reflection. The study underscores the value of incorporating avant-garde methods within film education to prepare students for a rapidly changing cinematic landscape.